Fracture behavior of short fiber-reinforced CAD/CAM inlay restorations after cyclic fatigue aging - Garoushi Sufyan; Barlas Deniz; Vallittu Pekka K; Uctasli Mine Betul; Lassila Lippo (Japan, 2025)
The aim of this study was to assess the fracture behavior of molar teeth restored with MOD inlays made of experimental short fiber-reinforced CAD/CAM composite block (SFRC CAD) before and after cyclic fatigue aging. Standardized MOD cavities were prepared on 60 intact mandibular molars. Three groups of CAD/CAM made inlay restorations (Cerasmart 270, Enamic, and SFRC CAD) were fabricated (n = 20/group). All restorations were luted with self-adhesive dual-cure resin cement (G-Cem One). Half of restored teeth per each group (n = 10) were quasi-statically loaded until fracture without aging. The other half underwent cyclic fatigue aging for 500,000 cycles (Fmax = 150 N) before being loaded quasi-statically until fracture. Then, the fracture type was visually inspected. The microstructure and elemental content of CAD/CAM materials were assessed using SEM and EDS. Two-way analysis of variance (ANOVA) was used to statistically examine the data, and it was followed by the Tukey HSD test (α = 0.05). ANOVA demonstrated that both material type and aging had a significant effect (p < 0.05) on the load-bearing capacity values of the restorations. Teeth restored with SFRC CAD showed significantly the highest (p < 0.05) load-bearing capacity (2535 ± 830 N) after fatigue aging among all groups. SEM images showed the ability of short fibers in SFRC CAD composite to redirect and hinder crack propagation. With regard to fracture mode, Enamic group revealed 85% of catastrophic failure (vs. 45% and 10% for Cerasmart 270 and SFRC CAD, respectively). Large MOD cavities on molar teeth were most favorably restored with SFRC CAD inlays, yielding the highest load-bearing capacity and more restorable failures.